Microbial transformation of the Deepwater Horizon oil spill—past, present, and future perspectives - Kimes, Nikole E.; Callaghan, Amy V.; Suflita, Joseph M.; Morris, Pamela J. (Frontiers in Microbiology, 2014)
The Deepwater Horizon blowout, which occurred on April 20, 2010, resulted in an unprecedented oil spill. Despite a complex effort to cap the well, oil and gas spewed from the site until July 15, 2010. Although a large proportion of the hydrocarbons was depleted via natural processes and human intervention, a substantial portion of the oil remained unaccounted for and impacted multiple ecosystems throughout the Gulf of Mexico. The depth, duration and magnitude of this spill were unique, raising many questions and concerns regarding the fate of the hydrocarbons released. One major question was whether or not microbial communities would be capable of metabolizing the hydrocarbons, and if so, by what mechanisms and to what extent? In this review, we summarize the microbial response to the oil spill as described by studies performed during the past four years, providing an overview of the different responses associated with the water column, surface waters, deep-sea sediments, and coastal sands/sediments. Collectively, these studies provide evidence that the microbial response to the Deepwater Horizon oil spill was rapid and robust, displaying common attenuation mechanisms optimized for low molecular weight aliphatic and aromatic hydrocarbons. In contrast, the lack of evidence for the attenuation of more recalcitrant hydrocarbon components suggests that future work should focus on both the environmental impact and metabolic fate of recalcitrant compounds, such as oxygenated oil components.